Adaptive evolution and demographic history contribute to the divergent population genetic structure of Potato virus Y between China and Japan. (2nd March 2017) - Gao, Fangluan; Zou, Wenchao; Xie, Lianhui; Zhan, Jiasui
Abstract: Potato virus Y (PVY) is an important plant pathogen causing considerable economic loss to potato production. Knowledge of the population genetic structure and evolutionary biology of the pathogen, particularly at a transnational scale, is limited but vital in developing sustainable management schemes. In this study, the population genetic structure and molecular evolution of PVY were studied using 127 first protein (P1) and 137 coat protein (CP) sequences generated from isolates collected from potato in China and Japan. High genetic differentiation was found between the populations from the two countries, with higher nucleotide diversity in Japan than China in both genes and a K ST value of .216 in the concatenated sequences of the two genes. Sequences from the two countries clustered together according to their geographic origin. Further analyses showed that spatial genetic structure in the PVY populations was likely caused by demographic dynamics of the pathogen and natural selection generated by habitat heterogeneity. Purifying selection was detected at the majority of polymorphic sites although some clade‐specific codons were under positive selection. In past decades, PVY has undergone a population expansion in China, whereas in Japan, the population size of the pathogen has remained relatively constant.